Selection of excipients for the purpose of creating an intranasal gel of interleukin-1 receptor antagonist β (IL-1ra) - B. S. Burlaka; I. F. Bielenichev; V. V. Hladyshev; E. V. Suprun; H. P. Lysianska (Zaporozhye State Medical University, 2020)
There is a negative dynamic of the spread of cerebrovascular diseases, which often lead to disability or death in patients in the world, today. Such diseases are characterized by acute disorders of cerebral metabolism and blood circulation, against the background of other chronic pathologies. More than one hundred thousand cases of stroke are registered in Ukraine every year, with more than thirty percent of patients dying within the first month of the disease according to the Center for Medical Statistics of the Ministry of Health of Ukraine. The nasal route of administration is a promising method of transporting active substances for systemic action, various pharmacotherapeutic groups, both small and large molecules. The created nasal preparations of hormones, antibiotics, analgesics, exhibit a quick therapeutic effect due to the branched capillary system in the nasal cavity. In addition, the nasal route of administration is the most promising non-invasive method for delivering active substances to the brain for cerebroprotective drugs, due to the anatomical features of the location of the nerves. According to published data, the researchers found that the receptor antagonist of interleukin-1 (IL-1ra) exhibits neuroprotective properties in brain ischemia by blocking excess IL-1 and activating the anti-inflammatory cytokine cascade, in order to reduce local inflammation and neuronal loss. Therefore, in order to expand the range of pharmacotherapeutic drugs - neuroprotectors, the development of a new intranasal form with the active pharmaceutical ingredient - receptor antagonist interleukin-1 (IL-1ra) is an urgent problem of modern medicine and pharmacy. The aim of work was to substantiate the choice of excipients for the new intranasal gel of the receptor antagonist of interleukin-1 (IL-1ra). Materials and methods. The studies were carried out according to the plan of two-way analysis of variance with repeated observations. Factors that were investigated: factor A (type of polymer) - A1 - chitosan 3 %, A2 - sodium carboxymethyl cellulose 0.3 %, A3 - sodium hyaluronate 0.7 %, A4 - sodium alginate 0.5 %; factor B (type of alcohol): B1 - without alcohol, B2 - sorbitol, B3 - glycerin, B4 - D-panthenol. A prefabricated solution of the receptor antagonist of interleukin-1 (IL-1ra) was used as an active substance. A portion of the active substance was taken considering the calculations, to ensure a concentration of 0.5 % IL-1ra in each composition. The release of the active pharmaceutical ingredient was determined by equilibrium dialysis according to Kruvchinsky at 37.0 ± 0.5 °C through a semi-permeable membrane - "Cuprofan" for all compositions. Dialysis was performed in Franz cells at a nine-position station (PermeGear, Inc., USA). The concentration of IL-1ra, after 30 minutes, was determined by UV spectrophotometry at a wavelength of 280 nm on a UV-2600 spectrophotometer (Shimadzu Corporation, Japan). Results. We studied the effect of pharmaceutical factors (polymers and alcohols) on the intensity of the release of IL-1ra from the nasal form to justify the choice of excipients for the nasal gel of the receptor antagonist interleukin-1 β. The results of the analysis of variance of pharmaceutical factors (polymers and alcohols) showed that hydrophilic polymers and humectants had a significant effect on the release of the active substance from the experimental compositions. It is advisable to use a mucoadhesive polymer - sodium salt of carboxymethylcellulose, as well as alcohol-moisturizer D-panthenol for the new nasal form of IL-1ra, as excipients. Conclusions. Excipients were selected for a liquid intranasal gel with the receptor antagonist interleukin-1 (IL-1ra). It was found that the type of mucoadhesive polymers and alcohols, to moisten the mucous membrane, had a significant effect on the release of the active pharmaceutical ingredient from nasal dosage forms. As a result of research, it was found that the optimal release of IL-1ra from nasal compositions was provided by excipients - hydrophilic mucoadhesive component - sodium carboxymethylcellulose with the addition of humectant alcohol - D-panthenol.